Prawo do poznania matki biologicznej według krajowego prawa rodzinnego: [The Right to Recognize Biological Mother Under the Polish Family Law] (Studia Prawnicze / The Legal Studies, 2014)
Osoba matki jest niewątpliwie fundamentem rodziny w sensie zarówno społecznym, jak i prawnym. Prawne ustalenie pochodzenia dziecka od określonej kobiety tworzy nie tylko stan cywilny dziecka, ale również świadomość swojego genetycznego pochodzenia, która – jak twierdzi L. Stecki – jest niezwykle istotnym elementem odróżniającym człowieka od innych zwierząt. Tak rozumiana świadomość wpływa na tożsamość człowieka, jest zatem elementem kształtującym jego osobowość. Niniejszy artykuł dotyczy konsekwencji prawnych wprowadzenia do k.r.o. nowelizacją z 2008 r. regulacji prawnej macierzyństwa, a w szczególności kwestii dot. możliwości dochodzenia prawa do poznania swojego pochodzenia od matki. The subject of this article is an analysis whether on the grounds of Polish Code on Family and Guardianship it is possible to determine the one's right to recognize his/her mother. Introduction to the Polish Code on Family and Guardianship a legal definition of mother and claims for establish or denial of one's motherhood was legislator's attempt to regulate the civil status of child. Development of the in vitro treatment may lead to situation where one women would be donor of a germ cells while other women would bear a child. The article therefore provides an analysis of legal consequences of this amendment to the code in respect to legal regulation on motherhood. In particularly the issues of admissibility of claims for recognize one's genetic and biological mother as well as evidence limitation in this kind of cases would be addressed in the article.